Characterizing the Effects of Nasal Prong Interfaces on Aerosol Deposition in a Preterm Infant Nasal Model - Karl Bass; Mohammad A. M. Momin; Connor Howe; Ghali Aladwani; Sarah Strickler; Arun V. Kolanjiyil; Michael Hindle; Robert M. DiBlasi; Worth Longest (AAPS PharmSciTech, 2022)
The objective of this study was to characterize the effects of multiple nasal prong interface configurations on nasal depositional loss of pharmaceutical aerosols in a preterm infant nose-throat (NT) airway model. Benchmark in vitro experiments were performed in which a spray-dried powder formulation was delivered to a new preterm NT model with a positive-pressure infant air-jet dry powder inhaler using single- and dual-prong interfaces. These results were used to develop and validate a computational fluid dynamics (CFD) model of aerosol transport and deposition in the NT geometry. The validated CFD model was then used to explore the NT depositional characteristic of multiple prong types and configurations. The CFD model highlighted a turbulent jet effect emanating from the prong(s). Analysis of NT aerosol deposition efficiency curves for a characteristic particle size and delivery flowrate (3 µm and 1.4 L/min (LPM)) revealed little difference in NT aerosol deposition fraction (DF) across the prong insertion depths of 2–5 mm (DF = 16–24%) with the exception of a single prong with 5-mm insertion (DF = 36%). Dual prongs provided a modest reduction in deposition vs. a single aerosol delivery prong at the same flow for insertion depths Graphical Abstract